Colorectal cancer and hereditary colon cancer syndromes - Burke, Carol A. (Henry Stewart Talks, 2011)
Colorectal cancer is a molecularly heterogeneous disease known to arise from two distinct origins, the adenomatous and serrated pathways, Sessile serrated polyps, also known as sessile serrated adenomas, and traditional serrated adenomas are believed to be the precursor lesions for serrated carcinomas which account for up to 30% of sporadic colorectal cancers, When colorectal polyps or cancer occur in multiple generations, numerous relatives, at a young age of onset or in association with unusual numbers of lesions or extra-colonic tumors, a hereditary colorectal cancer syndrome should be suspected as a potential cause, The ability to recognize a patient with a hereditary colorectal cancer syndrome allows a practitioner to stratify her or his patient's lifetime cancer risk and devise prevention and management strategies for risk reduction in the patient and family once the diagnosis is confirmed